The Effect of Activated Charcoal Coffee Grounds (Coffea Sp.) as an Adsorbent on the Quality of the Liquid Sugar of Siwalan - Roy Darus (Jurnal Sains dan Terapan Kimia, 2022)
This study aimed to determine the adsorbent characteristics of coffee grounds activated charcoal (Coffea Sp.), optimum adsorption contact time, and differences in the quality of siwalan liquid sugar through adsorption and without adsorption. The characteristics of coffee grounds activated charcoal were determined by FTIR and SAA. FTIR characterization showed that activated coffee grounds charcoal contained functional groups of O-H, Csp2-H, Csp3-H, C-H2 methylene, C-O, and C=C-H. Characterization with SAA showed that the surface area of activated charcoal was 27.70 m2/g with a pore volume of 0.02 ml/g and an adsorption pore size of 1.63 nm. The optimum contact time of the adsorbent in the adsorption of impurities in the palm sap was 60 minutes. The siwalan liquid sugar, which went through adsorption, had a reducing sugar content of 6.70%, and the one without adsorption was 10.18%. While the ash content of siwalan liquid sugar through adsorption was 4.73%, and without adsorption was 6.5%. This value indicates that the quality of siwalan liquid sugar through adsorption is higher than that which does not go through the adsorption stage. Keywords: adsorption, activated charcoal, siwalan liquid sugar